Reactogenicity and safety of COVID-19 primary immunisation and booster vaccination regimens: a comparative observational cohort study - Warkentin, Lisette; Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastiao, Maria; Hueber, Susann (BMC Medicine, 2023)
Background: Since the beginning of the COVID-19 vaccination campaigns, recommendations regarding the vaccination have been very dynamic. Although the safety and efficacy of different vaccines have been analysed, data were scarce for vaccine regimens combining different vaccines. We therefore aimed to evaluate and compare the perceived reactogenicity and need for medical consultation after the most frequently applied homologous and heterologous COVID-19 vaccination regimens. Methods: In an observational cohort study, reactogenicity and safety were assessed within a maximum follow-up time of 124 days using web-based surveys. Reactogenicity was assessed for different vaccination regimens 2 weeks after a vaccination (short-term survey). The following surveys, long-term and follow-up surveys, focused on the utilisation of medical services, including those that were not suspected to be vaccine-related. Results: Data of 17,269 participants were analysed. The least local reactions were seen after a ChAdOx1 − ChAdOx1 regimen (32.6%, 95% CI [28.2, 37.2]) and the most after the first dose with mRNA-1273 (73.9%, 95% CI [70.5, 77.2]). Systemic reactions were least frequent in participants with a BNT162b2 booster after a homologous primary immunisation with ChAdOx1 (42.9%, 95% CI [32.1, 54.1]) and most frequent after a ChAdOx1 − mRNA-1273 (85.5%, 95% CI [82.9, 87.8]) and mRNA-1273/mRNA-1273 regimen (85.1%, 95% CI [83.2, 87.0]). In the short-term survey, the most common consequences were medication intake and sick leave (after local reactions 0% to 9.9%; after systemic reactions 4.5% to 37.9%). In the long-term and follow-up surveys, between 8.2 and 30.9% of participants reported consulting a doctor and between 0% and 5.4% seeking hospital care. The regression analyses 124 days after the first and after the third dose showed that the odds for reporting medical consultation were comparable between the vaccination regimens. Conclusions: Our analysis revealed differences in reactogenicity between the COVID-19 vaccines and vaccination regimens in Germany. The lowest reactogenicity as reported by participants was seen with BNT162b2, especially in homologous vaccination regimens. However, in all vaccination regimens reactogenicity rarely led to medical consultations. Small differences in seeking any medical consultation after 6 weeks diminished during the follow-up period. In the end, none of the vaccination regimens was associated with a higher risk for medical consultation. Trial registration: DRKS DRKS00025881 (https://drks.de/search/de/trial/DRKS00025373 ). Registered on 14 October 2021. DRKS DRKS00025373 (https://drks.de/search/de/trial/DRKS00025881 ). Registered on 21 May 2021. Registered retrospectively.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; Survey; Vaccines